2017
DOI: 10.1186/s41155-017-0079-3
|View full text |Cite|
|
Sign up to set email alerts
|

Retirement preparation program: evaluation of results

Abstract: The present study aimed to evaluate the results obtained in the retirement preparation program (RPP) regarding changes in retirement planning behaviors, the meaning of work, and improvement in quality of life. It is a quasi-experimental research, using a pre-and post-test evaluation with a non-equivalent control group, including 82 participants, who were public workers near retirement. Among these, 50 participated in the RPP (experimental group (EG)) and 32 belonged to the control group (CG). All responded to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 11 publications
1
10
1
5
Order By: Relevance
“…In a study of workers in pre-retirement from a public institution in southern Brazil, the participants showed greater autonomy and freedom in decision-making, greater involvement in activities outside of work, and investment in personal projects and volunteering. 24 However, women have shown greater acceptance for such programs, which can be explained by their greater investment in healthy behavior and interpersonal relationships. 24 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of workers in pre-retirement from a public institution in southern Brazil, the participants showed greater autonomy and freedom in decision-making, greater involvement in activities outside of work, and investment in personal projects and volunteering. 24 However, women have shown greater acceptance for such programs, which can be explained by their greater investment in healthy behavior and interpersonal relationships. 24 …”
Section: Resultsmentioning
confidence: 99%
“… 24 However, women have shown greater acceptance for such programs, which can be explained by their greater investment in healthy behavior and interpersonal relationships. 24 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their effects can be softened by special training that prepares employees for retirement. Previous research has shown that such programs enhance one's dedication to working, improve satisfaction through an awareness of contributing to the common good, and decrease stress levels [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the factors which influence a worker's retired life are known, notably: physical health, finances, psychological factors, leisure, the voluntariness of retirement, and social interaction (Barbosa, Monteiro, & Murta, 2016). However, few interventions have been developed and evaluated with the objective of modifying these factors (Boehs, Medina, Bardagi, Luna, & Silva, 2017;Hurtado & Topa, 2019;Pazzim & Marin, 2017). A review by Leandro-França, Murta, Hershey, and Barbosa (2016) consulted 13 databases in search of retirement education studies written in Portuguese, Spanish, or English that included the description and evaluation of the procedures and results.…”
Section: Introductionmentioning
confidence: 99%